Gene Functional Prediction Using Clustering Methods for the Analysis of Tomato Microarray Data - Torres-Aviles, F; Romeo-Nunez, J (Springer Verlag, 2013)
Molecular mechanisms of plant-pathogen interaction have been studied thoroughly because of its importance for crop production and food supply. This knowledge is a starting point in order to identify new and specific resistance genes by detecting similar expression patterns. Here we evaluate the usefulness of clustering and data-mining methods to group together known plant resistance genes based on expression profiles. We conduct clustering separately on P.infestans inoculated and not-inoculated tomatoes and conclude that conducting the analysis separately is important for each condition, because grouping is different reflecting a characteristic behavior of resistance genes in presence of the pathogen. © Springer International Publishing Switzerland 2013.